The interactive assessments using gamification tools (Kahoot! & Socrative) - Lawrance, Paul Joseph (2022)
The Ph.D. research project “Gamification in Middle, Secondary and Higher Education to motivate learners and develop creative thinking” enabled me to introduce Gamification tools in GSS Jain Gurukul Cambridge International residential school, Chennai, India, to conduct Interactive Assessments in teaching. The feasibility study was carried out on the curriculum of Middle and Secondary education with the available technology of the institution, and Gamification tools. A questionnaire one was conducted to identify students’ participation, engagement, and selfinitiative in learning the module, and the usage of multimedia tools in classroom activities. Questionnaire one and the research study ensured to decide and introduce Gamification tools Kahoot! and Socrative for various classroom activities of GSS Jain Gurukul students. A case study was used as a method in this research. At the end of the academic year questionnaire two was applied to identify students' participation, engagement, motivation, creative thinking, and self-confidence in learning. The results show that almost all students strongly agreed on the above factors and that gamification strongly stimulated their enthusiasm and willingness to use such tools in their learning.